2011
DOI: 10.1021/ef200227r
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the NOx Emissions in a 1000 MW Tangentially Fired Pulverized-Coal Boiler: Influence of the Multi-group Arrangement of the Separated over Fire Air

Abstract: Computational fluid dynamics (CFD) investigations have been carried out to understand the combustion and NO x emission characteristics in a 1000 MW pulverized-coal boiler, which is equipped with a dual-circular tangential-firing system in a single furnace. One group of separated over fire air (SOFA) nozzles has been widely studied and used in controlling the NO x emissions in a pulverized-coal boiler. In this work, a multi-group of SOFA nozzle arrangement is investigated for the NO x control and reduction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 27 publications
1
45
0
Order By: Relevance
“…Various studies of the optimization of SOFA to improve boiler performance have been reported in the literature based on experiments and/or computational fluid dynamics (CFD). Increasing the SOFA ratio and optimizing its detailed distribution were found to be effective in reducing NOx emission for various boiler types [6][7][8][9][10][11][12][13]. However, the change in reaction stoichiometry can also significantly alter the combustion and heat transfer characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies of the optimization of SOFA to improve boiler performance have been reported in the literature based on experiments and/or computational fluid dynamics (CFD). Increasing the SOFA ratio and optimizing its detailed distribution were found to be effective in reducing NOx emission for various boiler types [6][7][8][9][10][11][12][13]. However, the change in reaction stoichiometry can also significantly alter the combustion and heat transfer characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it can be seen that the NO x released from coal‐fired power stations is increasing gradually year by year . To effectively control NO x emissions, a series of technologies are applied to coal‐fired power plants for reducing NO x , including Low NO x Burners (LNB), Over Fire Air (OFA), Selective Non‐Catalytic Reduction (SNCR) and Selective Catalytic Reduction (SCR) . Among these technologies, SCR technology is the best developed technique for efficiently eliminating NO x emissions due to its efficiency and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…This is not conducive to the formation of NOx, and makes the furnace exit NOx emissions reduction. Li et al (2015) and Zhou et al (2011) studied a 300MW coal-fired boiler and a 1000 MW tangentially fired pulverized-coal boiler of low NOx combustion retrofit, which increases the SOFA system, making air depth classification, can reduce the production of NOx. Li et al (2014) and Sun et al (2013) focused on the tangentially fired boiler with low nitrogen transformation and analyzed the furnace NOx emission characteristics.…”
Section: Introductionmentioning
confidence: 99%